High performance colored selective absorbers for architecturally integrated solar applications. Issue 14 (14th April 2015) - Chen, Feiliang; Wang, Shao-Wei; Liu, Xingxing; Ji, Ruonan; Yu, Liming; Chen, Xiaoshuang; Lu, Wei
<x xml:space="preserve">Abstract</x> High performance colored absorbers with a TiNxOy absorbing layer and a TiO2/Si3N4/SiO2 dielectric stack are designed and fabricated for architecturally integrated solar energy applications.